0846 Opioid Use and Sleep Architecture in Fibromyalgia. (12th April 2019) - Curtis, Ashley F; Miller, Mary B; Rathinakumar, Himangshu; Robinson, Michael; Staud, Roland; Berry, Richard B; McCrae, Christina S
Abstract: Introduction: Patients with Fibromyalgia (FM) are frequently prescribed opioids to treat chronic pain and sleep disturbances. However, opioid use is associated with self-reported/actigraphic sleep disruption, and research suggests opioid effects may depend on age, dosage, or pain intensity. Whether opioid use/dosage affect physiological sleep (polysomnography, PSG-assessed) in FM is unclear. The present study assessed associations between opioid use/dosage and physiological sleep in FM, and examined whether effects depended on age or pain intensity. Methods: Participants ( N =193, M age =51.7, SD =11.8) with FM and self-reported sleep disturbance underwent ambulatory PSG measuring sleep onset latency (SOL), wake time after sleep onset (WASO), total sleep time (TST), %stage-1 sleep, %stage-2 sleep, %stage-3/4 (slow wave sleep, SWS), %rapid eye movement (REM) sleep, and apnea hypopnea index (AHI). Participants completed 14 daily diaries recording evening pain intensity, and daily opioid/sleep medication use (Y/N). Medication names/dosage were recorded. Milligrams of opiates were converted to lowest recommended dosage (LRD). Multiple regressions determined whether opioid use or average LRD amongst opioid users independently predicted or interacted with age/pain intensity to predict sleep outcomes, controlling for use of sleep medication and AHI. Results: Opioid use predicted greater SOL and %stage-2 sleep, and predicted lower %SWS. Amongst opioid users ( n =65), LRD interacted with age to predict SOL ( B =2.59, SE=1.00, p =.01), accounting for 9% SOL variance. Specifically, higher dosage predicted longer SOL for older adults, whereas there was no association for middle-aged/younger adults. LRD interacted with pain intensity to predict %SWS ( B =.27, SE=.08, p =.002), accounting for 15% variance in %SWS. Specifically, higher dosage predicted reduced %SWS for individuals with lower pain, increased %SWS for individuals with higher pain, and did not predict %SWS for patients with average pain. Opioid use/dosage did not predict WASO, TST, %stage-1, or %REM. Conclusion: Results suggest opioid use in FM prompts changes in sleep architecture, specifically increasing amount of lighter sleep and reducing SWS. Opioid-related sleep disruption may be exacerbated at higher doses in older adults and in patients with low pain, whereas higher doses may promote deeper sleep in patients with high pain. Support (If Any): NIAMS (R01AR055160/R01AR005160-S1;PI, McCrae). Data collected at the University of Florida (Clinical Trial-NCT02001077;PI, McCrae).